2011
DOI: 10.1007/s11858-011-0352-3
|View full text |Cite
|
Sign up to set email alerts
|

Case-based pedagogy for prospective teachers to learn how to teach elementary mathematics in Korea

Abstract: Cases have been used in mathematics teacher education with increasing prominence. Yet, there is little research that confirms cases as pedagogical tools to improve prospective teacher expertise, specifically in Asian contexts. This article illustrates how a specific case-based pedagogy was developed and implemented in Korea to increase prospective elementary teacher expertise in terms of paying attention to the mathematics-specific features of a lesson. The results showed that the participant teachers' analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…For example, Alsawaie and Alghazo (2010) found that, when PSTs were asked to analyze video lessons with a framework, utilizing video helped PSTs to pay attention to noteworthy events in classroom interactions, and develop their ability to pay attention to children's learning when watching and analyzing a lesson. Similarly, Santagata, Zannoni and Stigler (2007) and Pang (2011) both found that the use of video enhanced PSTs' ability to attend to children's thinking beyond mere descriptions to more nuanced observations of the effects of teachers' actions on children's thinking. While not a specific focus on mathematics, Masats and Dooly (2011) in their study of the use of video case studies in a teacher education program found that PSTs reported they were better able to understand more of the complexities and nuances in teaching practice by engaging with the video case studies.…”
Section: Introductionmentioning
confidence: 93%
“…For example, Alsawaie and Alghazo (2010) found that, when PSTs were asked to analyze video lessons with a framework, utilizing video helped PSTs to pay attention to noteworthy events in classroom interactions, and develop their ability to pay attention to children's learning when watching and analyzing a lesson. Similarly, Santagata, Zannoni and Stigler (2007) and Pang (2011) both found that the use of video enhanced PSTs' ability to attend to children's thinking beyond mere descriptions to more nuanced observations of the effects of teachers' actions on children's thinking. While not a specific focus on mathematics, Masats and Dooly (2011) in their study of the use of video case studies in a teacher education program found that PSTs reported they were better able to understand more of the complexities and nuances in teaching practice by engaging with the video case studies.…”
Section: Introductionmentioning
confidence: 93%
“…We employed four main topics (i.e., Mathematical Tasks, Instructional Strategies, Learning Environment, and Mathematical Discourse), building on Pang (2011). We then subdivided each topic to capture various aspects in the PSTs' comments more precisely (see Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, observing a salient part of an entire lesson is different from understanding the overall situation of the lesson. Given that a mathematics lesson involves complex situations in which multiple factors are intertwined (Lampert, 2001), PSTs need to be able to observe the lesson as a whole to fully understand the interactions among the teacher, students, and content (Pang, 2011). This study examined how and what aspects PSTs pay attention to in an elementary mathematics lesson as a whole.…”
Section: Literature Review 1 Development Of Noticing Skills Through Teacher Education Programsmentioning
confidence: 99%
“…Common types of cases that are employed in mathematics teacher education include exemplars [20], narratives [21,22], video cases [23], and problem situations [24,25]. The case presented in this paper could be categorized as a specific type of problem situation case.…”
Section: Theoretical Backgroundmentioning
confidence: 99%